2021
DOI: 10.3390/ijms22010430
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis-Related Flavoproteins: Their Function and Stability

Abstract: Ferroptosis has been described recently as an iron-dependent cell death driven by peroxidation of membrane lipids. It is involved in the pathogenesis of a number of diverse diseases. From the other side, the induction of ferroptosis can be used to kill tumor cells as a novel therapeutic approach. Because of the broad clinical relevance, a comprehensive understanding of the ferroptosis-controlling protein network is necessary. Noteworthy, several proteins from this network are flavoenzymes. This review is an at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Also, the key differential metabolites of GSH, FMN, fumaric acid, etc. in these pathways have important roles in ferroptosis ( Ursini and Maiorino, 2020 ; Wang H et al, 2020 ; Vabulas, 2021 ). Combining the above metabolic pathway analysis, the hypothesis was proposed that EEE caused liver injury by inducing ferroptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the key differential metabolites of GSH, FMN, fumaric acid, etc. in these pathways have important roles in ferroptosis ( Ursini and Maiorino, 2020 ; Wang H et al, 2020 ; Vabulas, 2021 ). Combining the above metabolic pathway analysis, the hypothesis was proposed that EEE caused liver injury by inducing ferroptosis.…”
Section: Resultsmentioning
confidence: 99%
“…GABARAPL1 as the other protective gene and ferroptosis driver has been proven as a potential positive regulator of ferroptosis via RNAi screening 36 . For the dangerous markers, the SQLE gene encodes squalene epoxidase to catalyze the oxidation of squalene that could change the lipid profile of tumor cells and protect them from ferroptosis, 37 and the inhibition of the flavoprotein SQLE with NB‐598 could enhance ferroptosis 38 . RAD51AP1, as a DNA‐binding protein that stimulates RAD51 activity, could protect tumor cells against DNA damage and may be linked to cancer development and progression 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis is a new form of programmed cell death discovered in 2012 ( Dixon et al., 2012 ). Distinct from necrosis, autophagy, and apoptosis, ferroptosis is frequently caused by excessive lipid peroxidation ( Xu et al., 2019 ; Chen et al., 2019 ; Bebber et al., 2020 ), with features of iron accumulation, plasma membrane deficiency, cytoplasm and organelles swelling, chromatin condensation, and mitochondrial disorders ( Tang et al., 2021 ; Vabulas, 2021 ; Friedmann Angeli et al., 2014 ). Recently, some studies have revealed that ferroptosis is closely associated with the initiation and progression of CRC ( Nie et al., 2018 ; Li et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%